HUBUNGAN FAKTOR FASILITAS DAN PERSEPSI DENGAN PEMILIHAN TEMPAT PERSALINAN ANTARA BIDAN WILAYAH DAN LUAR WILAYAH - admin ilkes (STIKES Karya Husada Kediri, 2017)
Mother quantity at midwife outside area, will describe that area midwife performance likely unfavorable, less professional, less interested and service quality that given to lose with midwife outside area. This plan research detects factor that effect place selection in a birth between area and outside area. Research design analytic correlasional with approach cross sectional. population all mothers with total 57 mothers with sample 50 respondents was taken with technique simple random sampling. Free variable service facilities and perception, while bound accommodation selection. From research result got a large part respondent evaluates facilities in place that chosen good that 7 respondents (54%), a large part has positive perception about place that was 30 respondents (60%), almost entire respondents chooses midwife outside area that 40 respondents (80%) from total 50 respondents and there is no service facilities with place selection at area or outside area (p-value 0,129 > 0, 05 so Ho accepted with there service perception connection with place selection at midwife area or outside area at work area (pvalue 0,047 < 0,05) so ho aversed. Service perception influences place selection at midwife outside area as big as 44,3% (Nagelkerke = 0,443). Correlation strength belongs enough strong and positive (r = 0,666), mean more positive perception so place selection to midwife outside ever greater area and on the contrary. This matter caused service place at village midwife in general relative same. Which are positive perception about place effect somebody attitude about place which was on final also influential to place selection.